(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Mirzo Ulugbek (1394–1449) was a pioneering scholar and ruler during the Timurid Empire who contributed to an era of scientific flourishing. Establishing one of the world’s most advanced observatories in Samarkand, he helped usher in a renaissance of knowledge in astronomy, mathematics, and philosophy. This article explores Ulugbek’s scientific legacy, his observatory’s pivotal role in global knowledge, and the broader impact of his achievements on the Islamic Golden Age. Ulugbek’s work reflects the intellectual richness of this era, inspiring future generations in both the Islamic world and beyond.